Interplay of Sleep Quality, Insomnia and Quality of Life in Individuals Undergoing Hemodialysis: Insomnia and Quality of Life - Saboor, Farheen; Malik, Nudra (Pakistan Journal of Health Sciences, 2024)
Insomnia is the most commonly occurring disorder of sleep experienced by individuals with chronic kidney disease. It is associated with physical and psychological health issues specifically the ones on hemodialysis. Objectives: Insomnia is the most commonly occurring disorder of sleep experienced by individuals undergoing hemodialysis. It is associated with physical and psychological health issues and could reduce the quality of life of these patients. The aim of the current study is to find out the frequency of insomnia as well as to examine the relationship between sleep quality and quality of life in individuals on hemodialysis. Methods: It was a cross sectional study and non-probability purposive sampling technique was used for selecting the sample of patients undergoing hemodialysis from a dialysis center of Lahore. The sample consisted of both men and women (N=100) with age range 40 and above (M=51.40, SD=7.25). Insomnia, general sleep scale and quality of life scale were used to collect data from the participants. Results: Insomnia was found to be prevalent in 6% of the patients. QOL was significantly poor in individuals with insomnia and poor sleep quality as compared to the ones with better sleep. Older age, increasing duration of hemodialysis and poor sleep quality were significant predictors of quality of life in our sample. Conclusions: Insomnia and/or poor quality sleep have a detrimental effect on patients’ quality of life in kidney disease. These findings can provide basis for awareness campaigns and health promotion programs aimed at timely diagnosis and management of insomnia and improvement in sleep quality as well as quality of life in individuals undergoing hemodialysis.